Financial Literacy, Financial Technology and Saving Behavior - Irdawati Irdawati; Abdul Rakhman Laba; Muhammad Yunus Amar; Fauzi R Rahim (Universitas Kristen Indonesia Toraja, 2022)
This research aims to examine the direct and indirect effects of financial literacy on saving behavior through financial technology as a mediating variable. Further, this research uses a quantitative approach with path analysis. This research picked millennial workers in Kendari City, Southeast Sulawesi, as sample of the research. Therefore, the results revealed that financial literacy directly has a significant effect on financial technology and saving behavior then, financial technology also has a significant positive effect on saving behavior. However, financial technology does not able to mediate the relationship between financial literacy and saving behavior significantly. This indicates that financial technology has not provided good facilitation for millennials, especially for helping them in looking the appropriate savings products their needed.